2020
DOI: 10.1073/pnas.2005447117
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potent thrombin inhibitors from a protease-focused DNA-encoded chemical library

Abstract: DNA-encoded chemical libraries are collections of compounds individually coupled to unique DNA tags serving as amplifiable identification barcodes. By bridging split-and-pool combinatorial synthesis with the ligation of unique encoding DNA oligomers, million- to billion-member libraries can be synthesized for use in hundreds of healthcare target screens. Although structural diversity and desirable molecular property ranges generally guide DNA-encoded chemical library design, recent reports have highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Using a split-and-pool strategy, each individual library of ∼100 million compounds was synthesized with a unique core scaffold. Quality assurance of libraries for selections was ensured through optimization and validation of on-DNA chemistry reactions prior to library synthesis and the precision of our DNA barcode reads using Illumina sequencing after library synthesis ( 13 , 20 22 ). These individual DEC-Tec libraries were subsequently pooled and screened as multibillion compound mixtures against His-tagged recombinant bromodomain proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a split-and-pool strategy, each individual library of ∼100 million compounds was synthesized with a unique core scaffold. Quality assurance of libraries for selections was ensured through optimization and validation of on-DNA chemistry reactions prior to library synthesis and the precision of our DNA barcode reads using Illumina sequencing after library synthesis ( 13 , 20 22 ). These individual DEC-Tec libraries were subsequently pooled and screened as multibillion compound mixtures against His-tagged recombinant bromodomain proteins.…”
Section: Resultsmentioning
confidence: 99%
“…DEC-Tec has been utilized by several pharmaceutical companies and academic institutions to develop potent and specific small-molecule inhibitors to various target proteins, including EPHX2 ( 7 ), RIP1 kinase ( 8 ), Mycobacterium tuberculosis InhA ( 9 ), autotaxin ( 10 ), BTK ( 11 ), the β 2 -adrenergic receptor ( 12 ), etc. Using the libraries that we created, our DEC-Tec screening against thrombin ( 13 ) and OXA-48 carbapenemase ( 14 ) also resulted in nanomolar small-molecule inhibitors for further development.…”
mentioning
confidence: 99%
“…Whereas, Cuozzo et al screened a DECL library of 225 million compounds, and identified a single compound (X-165) with a high activity against the production of lysophosphatidic acid, and this compound has been approved by the FDA for Phase I Clinical trials [197]. In other examples of using this strategy, Dawadi et al discovered a thrombin inhibitor using DECL [198], while, Kung et al identified two compounds that presented inhibition/binders to e Nα-terminal acetyltransferase (Naa50) using ECL library screening [199].…”
Section: Compound Screeningmentioning
confidence: 99%
“…Trypsin and thrombin : Focused split‐and‐pool DNA‐encoded libraries were designed by the groups of Neri and Matzuk, respectively, around the oxyanion hole‐binders benzamidine and guanidine to probe the surface around the active site of the serine proteases trypsin and thrombin, respectively. Successful identification of nanomolar inhibitors of trypsin 27 (Figure 7), and thrombin 28 (Figure 7), showed the potential of combinatorial libraries to identify highly potent protease inhibitors by densely covering chemical space around weakly active starting points [131,132] …”
Section: Proteasesmentioning
confidence: 99%